Playgroups as sources of social support for mothers - Hancock, K (My University, 2011)
Playgroups are regular, informal gatherings of parents and young children that provide a range of developmental opportunities for children, as well as opportunities for parents to develop social and support networks. While recent research has demonstrated that children from disadvantaged families tend to perform better on measures of learning and social outcomes when they persistently attend playgroup (Hancock et al., 2011), there is still very little research demonstrating any association between playgroup attendance and parental outcomes. The purpose of this study therefore was to examine the friendship networks and social support outcomes of mothers of young children according to patterns of playgroup attendance over time. This study used data from the B-cohort of the Longitudinal Study of Australian Children across three waves to examine the level of support that mothers received from friends over time. Multinomial logistic regression modelling indicated that mothers of 4-5 year olds who participated in playgroups when their child was 0-1 and 2-3 years were more likely to have consistently good support from friends, or to have improved support from friends compared with mothers who did not participate in playgroups with the study child. These results provide some evidence that playgroups are associated with improved social networks over time, and that socially isolated parents may find playgroups a useful resource to build their social networks.
Keywords: Children -- Early childhood; Social Capital -- Social support; Childhood and child development; Social Capital; Children; Social support; Early childhood; Childhood and child development